2017
DOI: 10.1128/aac.02490-16
|View full text |Cite
|
Sign up to set email alerts
|

Peak Measurement for Vancomycin AUC Estimation in Obese Adults Improves Precision and Lowers Bias

Abstract: Vancomycin area under the curve (AUC) estimates may be skewed in obese adults due to weight-dependent pharmacokinetic parameters. We demonstrate that peak and trough measurements reduce bias and improve the precision of vancomycin AUC estimates in obese adults (n ϭ 75) and validate this in an independent cohort (n ϭ 31). The precision and mean percent bias of Bayesian vancomycin AUC estimates are comparable between covariate-dependent (R 2 ϭ 0.774, 3.55%) and covariate-independent (R 2 ϭ 0.804, 3.28%) models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The mean (SD) Vc of vancomycin was 69.8 (16.9) liters in normal weight subjects compared with 74.7 (15.7) liters in obese subjects. This finding is consistent with studies that suggest improved prediction of vancomycin Vc with use of a traditional body-size-independent model (16,17). This classical error is also illustrated in Fig.…”
Section: Pharmacomorphomic Analyses Of Vancomycinsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean (SD) Vc of vancomycin was 69.8 (16.9) liters in normal weight subjects compared with 74.7 (15.7) liters in obese subjects. This finding is consistent with studies that suggest improved prediction of vancomycin Vc with use of a traditional body-size-independent model (16,17). This classical error is also illustrated in Fig.…”
Section: Pharmacomorphomic Analyses Of Vancomycinsupporting
confidence: 91%
“…Our previously published vancomycin pharmacokinetic model and covariance matrix was used as the Bayesian prior to compute 1-compartment and 2-compartment parameter estimates (17). The Bayesian analyses were accomplished using the maximum a posteriori (MAP) function in ADAPT 5 (BMSR, University of Southern California, Los Angeles, CA) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Results from a pilot study in 12 obese patients recently suggested that use of Bayesian software tools with peak and trough data provided more accurate AUC predictions than trough‐only data . If Bayesian tools are not available to perform dose revisions, use of two point measurements (peaks and troughs) should still be considered because it improves precision and lowers the bias of AUC estimates in obese adults …”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%
“…66 If Bayesian tools are not available to perform dose revisions, use of two point measurements (peaks and troughs) should still be considered because it improves precision and lowers the bias of AUC estimates in obese adults. 14,67 Summary A reasonable approach to initial vancomycin dosing in obese patients would be to reduce the loading dose (if indicated) to 20-25 mg/kg TBW and to reduce the starting maintenance dose, then adjust according to TDM. Software capable of Bayesian analysis should be used, if available, and/or peak and trough measurements (using Sawchuck and Zaske methods) 14 because it provides greater accuracy of AUC-guided dose revisions in obese patients.…”
Section: Vancomycinmentioning
confidence: 99%
“…8,14 In contrast, the Bayesian software evaluated had a correlation (AUC T to AUC REF ) of 70-85% (r 2 of 0.70-0.85; data not shown) when using the trough only; these values are similar to other published literature with trough-only Bayesian estimation. 26 Although some methodologies produced more accurate estimates, all methodologies produced average accuracy ratios of 0.80 or higher and bias of less than 20% (with the exception of DoseMe with AUC T ). This degree of accuracy is likely adequate when targeting an AUC of 400-600 hrÁmg/L.…”
mentioning
confidence: 95%